EFFECTIVE COMMUNICATION WITHIN THE COACHING STAFF ROUNDTABLE - Scariolo, Sergio; Cuzzolin, Francesco; Dzikic, Aleksandar; Mihajlovic, Filip (Sport- és Egészségtudományi füzetek, 2025)
Coach Džikić emphasised at the beginning of the conversa-tion that he always tries to set some standards in his teams, for the players and the staff as well. He highlighted that per-haps this is because of his cultural background, he does not like to praise his colleagues too much but tries to encour-age everyone to focus on their work and do it to the best of their ability. He also considers it is important to be as loyal as possible to his colleagues. He stressed the importance of the role of the volunteers, he is always asking them do they want to come to the training sessions, but he always keeps one rule: if someone wants to participate in the training, he/she must do it on court, being an active part of the session. His focal point is that everyone in the changing room can say whatever they want, but as soon as they walk out the door, everyone must follow the same path and there is zero tolerance for “I told you so” comments.